Science learning to understand the value of conservation character in students in the coastal region - Elya Nusantari; Ramli Utina; Abubakar Sidik Katili; Yowan Tamu (Universitas Ahmad Dahlan, 2020)
This research was conducted to understand the value of conservation character in students by utilizing local resources in the coastal areas of Gorontalo Province. The research design used is the application of one group pretest-posttest design. Data collection was performed using cluster sampling techniques with research subjects totaling 160 students spread across four elementary schools in the coastal areas of Gorontalo Province. Data analysis was performed using N-Gain and Anava 2 x 2 test to see differences in learning outcomes in the form of moral knowledge and moral goodness of conservation at each grade level and examine the difference in the total score of the pretest and the total score of the posttest. The results showed that the N-Gain value for knowledge about coastal natural resources was 0.74, moral conservation knowledge was 0.76, and moral goodness conservation was 0.84. Anava test results showed the level of class and type of test differed significantly on the character values of students with sig <0.05 (0.000 <0.05). That is, there are differences in the value of student conservation characters based on grade levels. Significantly the character value of grade 3 and grade 4 students shows the highest value compared to the grade value of grade 5 and grade 6 students. The application of science learning tools with conservation characteristics utilizing the local potential of natural resources in elementary school students in coastal areas can understand the character conservation of students in coastal areas.